First best implementation with costly information acquisition - Daniil Larionov; Hien Pham; Takuro Yamashita; Shuguang Zhu (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
We study mechanism design with flexible but costly information acquisition. There is a principal and four or more agents, sharing a common prior over the set of payoff-relevant states. The principal proposes a mechanism to the agents who can then acquire information about the state of the world by privately designing a signal device. As long as it is costless for each agent to acquire a signal that is independent from the state, we show that there exists a mechanism which allows the principal to implement any social choice rule at zero information acquisition cost to the agents.
Keywords: 330